CHANGING ATTITUDES TOWARDS LABOR IN A MARKET ECONOMY (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
The quality and level of productivity of human activity can be measured and determined in various ways. In scientific sources, these criteria are defined and described in different ways, based on different grounds